Plant diversity and evolution: Genotypic and phenotypic variation in higher plants - Henry, Robert J (Cabi, 2012)
An understanding of plant diversity at both the genome and phenome levels is important for biodiversity conservation and plant breeding. Recent advances in genomics have also resulted in a growth of the subject of plant functional genomics. This book brings these areas together by reviewing aspects of plant evolution as it relates to variation in plant genomes, and associated variations in plant phenomes. It will be of significant interest to those working within the areas of plant genetics, evolution, biodiversity, botany and agriculture